To evaluate the role of sputum in the diagnosis of lung cancer in south Indian population - M, Muniyappa; Rao, Vatsala S.; KB, Vidya (International Journal of Research in Medical Sciences, 2017)
Background:The main advantage of sputum cytology is its simplicity, non-invasiveness and minimal discomfort to the patient. Though, the sputum is evaluated in the diagnosis of lung cancer, the report on the same in the South Indian population was lacking. Therefore, the present study has been undertaken to evaluate the role of sputum in the diagnosis of lung cancer in South Indian population. Methods:The material consisted of sputum samples from 133 patients and was collected in clean wide mouthed disposable plastic containers. Patients were asked to collect sputum the next morning after washing the mouth properly. The sputum was immediately brought to the laboratory and poured into a watch glass. Four smears were prepared from each sample, out of which two smears were immediately fixed in methanol and the other two were air-dried. The methanol fixed smears were stained with Papanicolaou stain. Out of the two air dried smears, one was stained with May Grunwald Giemsa and the other with Gabbot's method for AFB. The smears were screened for malignant cells and a cytological diagnosis was made. The cytological diagnosis was correlated with the histopathological diagnosis. The data obtained were represented as mean percentages. Results:The observation of sputum smears showed numerous pleiomorphic keratinized squamous cells, keratinized squamous cell with hyper chromatic nucleus in well differentiated squamous cell carcinoma, pleiomorphic cells having vacuolated cytoplasm and vesicular nucleus with prominent nucleoli as in adenocarcinoma of the lung, cells arranged in small clusters and having scanty cytoplasm in small cell carcinoma and cells are slightly larger than lymphocyte with scanty cytoplasm and hyper chromatic, grooved nuclei in small cell carcinoma. Conclusion:Cytology of sputum is extremely useful and highly sensitive. The diagnostic accuracy is directly proportional to the number of samples. Sputum cytology is highly sensitive for the centrally located squamous cell carcinoma rather than the peripherally located adenocarcinoma. Properly collected, simple sputum examination alone can give results similar to other highly expensive methods like bronchoscopic material for the diagnosis of lung cancer.